Islamic position on physics with reference to Ibn Al-Haytham - Shuriye, Abdi Omar (2011)
This research contends that the study of the tabi'iyat (physics), in its specific form that we know today, was initially formulated by Muslim scholars. It was the Muslims who engender physics from the Aristotelian general outlines of form and matter. History reveals that Abu Ali al-Hasan ibn al-Hasan ibn al-Haytham was the first scholar to scientifically test the premise of hypothetical questions in research with demonstrable experiments. More than two hundred years later his books were read in Europe. Today he is known in Europe as Alhazen, Alhacen, or Alhazeni. The research at hand is part of explorations of his views on physics.